Photodegradation of Propaquizafop in Water Under UV Irradiation: The Identification of Transformation Products and Elucidation of Photodegradation Pathway - Zhijia Cheng; Zhongbin Lu; Zhiwei Shao; Bowen Huang; Yang Xiong; Hongqiang Fei; Xian Wu; Yanwei Liu; Mei Li; Zhiguang Hou; Zongzhi Lu (Agronomy)
The photolysis kinetics of propaquizafop in water under ultraviolet light was investigated in this study, and the effects of different influencing factors (pH, <semantics><msubsup>NO3−</msubsup></semantics>, metal ions) on the photolysis of propaquizafop were clarified. Propaquizafop residues in water were determined by a HPLC-UV detector. The results showed that the pH of the aqueous solution had no significant effect on the photolysis of propaquizafop (p < 0.05). The low <semantics><msubsup>NO3−</msubsup></semantics>, concentration (0.5~2 mmol/L) had a weak inhibitory effect on the photolysis of the propaquizafop; when the concentration of <semantics><msubsup>NO3−</msubsup></semantics> was 4 mmol/L, the degradation half-life of the propaquizafop was significantly higher than with other treatments (p < 0.05); Different concentrations of Fe3+ had varying degrees of inhibitory effects on the photolysis of propaquizafop. The inhibitory effect was stronger at low concentrations (0.5 mmol/L and 1 mmol/L) and weaker at high concentrations (2 mmol/L and 4 mmol/L). As the concentrations of Cu2+, Cd2+, Mn2+, Zn2+, and Ni2+ increased, their inhibitory effect on the photolysis of propaquizafop in an aqueous solution became stronger. In addition, LC–QTOF-MS was used to identify the photoproducts of propaquizafop in aqueous solution in this study. Five types of photoproducts were identified, and several propaquizafop degradation pathways and mechanisms were proposed, mainly including rearrangement, cracking reactions, dechlorination reactions, and light-induced redox reactions. The results of this study will help us to better understand the photodegradation law of propaquizafop in aqueous solution and provide data support for its safety evaluation in water.